Literature Review: Parental Strategies for Supporting the Cognitive Development of Early Childhood Education Students in the Digital Age - Dwitirta Mayasari; Nada Salwa; Siti Zulfiana (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
The presence of digital technology in this modern era has influenced various aspects of society, including parenting patterns and the development process of early childhood. The presence of digital technology can have both negative and positive impacts on the growth and development of early childhood. This literature review examines various literature on parental strategies in supporting early childhood development in the digital era. The literature comes from scientific articles from national and international journals spanning the years 2020-2025. The review in this study reveals four parental strategies in supporting children's cognitive development in the digital era, including: 1) parental digital literacy, 2) digital parenting, 3) utilization of media and educational games for cognitive stimulation, 4) collaboration between parents and schools in stimulating children's cognitive development.